2017
DOI: 10.15544/jws.2017.002
|View full text |Cite
|
Sign up to set email alerts
|

Waste and Its Characterization in Closed Recirculating Aquaculture Systems – A Review

Abstract: Abstract. Just like every economic activity, aquaculture has a particular effect on environment, which manifests itself due to waste through declining quality of subterranean water and eutrophication of surrounding surface water. Less than half of the feed in aquaculture is digested and assimilated, the rest ending up as waste either solid or dissolved and the nutrients phosphorus (P) and nitrogen (N) that are derived from fish excretion, faeces, and uneaten feed. The advantage of recirculating aquaculture sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In freshwater bodies, phosphorus is the main limiting factor for development of flora. Unused feed phosphorus in aquaculture, make its way to environment and encourages eutrophication (Mongirdas et al, 2017). In the present study results showed that fish retained at least 2.74 ± 0.37 % of the feed phosphorus content.…”
Section: Phosphorus Budgetsupporting
confidence: 55%
See 2 more Smart Citations
“…In freshwater bodies, phosphorus is the main limiting factor for development of flora. Unused feed phosphorus in aquaculture, make its way to environment and encourages eutrophication (Mongirdas et al, 2017). In the present study results showed that fish retained at least 2.74 ± 0.37 % of the feed phosphorus content.…”
Section: Phosphorus Budgetsupporting
confidence: 55%
“…Our results are also similar to those reported by Summerfelt et al, (2001) who calculated that every kilogram of fed feed emits 0.43 kg of suspended solids, additional 9% suspended solids of feed emerge from activity of heterotrophic organisms and another 0.09% due to activity of nitrification bacteria. Mongirdas et al, (2017) reported that it is unreal to expect less than 200 g of sediment in real growing conditions, and values higher than 450 g does not appear as well, because that would suggest uneconomical use of feed and would extremely increase the first cost of fish production.…”
Section: Tssmentioning
confidence: 99%
See 1 more Smart Citation
“…So in this system, it is necessary to treat the water continuously to remove the waste products excreted by the fish and also add oxygen so that the fish will be provided with enough oxygen to be alive and well (Bregnballe, 2015). In the RAS to ensure the optimal condition of various water quality, many physical and chemical parameters need to be controlled including ammonia, nitrites, nitrates, carbon dioxide, biological oxygen demand (BOD), alkalinity, pH, and others (Mongirdas et al, 2017). Biofilters and solids removal are the most important to optimize the water quality for healthy fish and good system performance (Badiola et al, 2012).…”
Section: Water Qualitymentioning
confidence: 99%
“…Diet is the major operating cost in fed monoculture systems [4]. Moreover, it is the primary waste source in fish and shrimp monocultures [5][6][7]. This situation is because a single species is not able to assimilate most diet nutrients and energy.…”
Section: Introductionmentioning
confidence: 99%